Multispecies fisheries management of the Sultanate of Oman using bioeconomic model - Sachinandan Dutta; Majid Al Harthy; Saud M. Al Jufaili; Ibtisam Al Abri (Heliyon)
A bioeconomic analysis using the Gordon-Schafer surplus production model was conducted on Indian mackerel (Rastrelliger kanagurta), Yellowfin tuna (Thunnus albacares), Kingfish (Scomberomorus commerson), and Indian Oil Sardine (Sardinella longiceps) based on data from the Ministry of Agriculture, Fisheries, Wealth, and Water Resources of Oman from 1990 to 2020. The alignment of biological and economic yields with the ideal fishing efforts needed to attain maximum sustainable yield (MSY) and maximum economic yield (MEY) was considered in order to evaluate the economic efficiency of existing fisheries management. The long-term sustainability of Oman's fisheries is improved by this analysis, which identifies inefficiencies in resource use and suggests viable remedies. Rastrelliger kanagurta exhibited the highest growth rate (r = 0.260), with similar catchability coefficients (q) between R. kanagurta (2.18E-05) and S. commerson (2.93E-05), and T. albacares (8.48E-06) and S. longiceps (8.41E-06). Optimal fishing effort was calculated using the catch per unit effort (CPUE) hypothesis. The effort to achieve maximum sustainable yield (EMSY) for R. kanagurta, T. albacares, S. commerson, and S. longiceps were estimated at 5982, 6614, 2222, and 6913, respectively. The harvest limit to achieve maximum economic yield (HMEY) was 9987.41 tons for R. kanagurta, 12928.77 tons for T. albacares, 2267.75 tons for S. commerson, and 135490.31 tons for S. longiceps. A discount rate of 10–20 % was suggested for long-term expansion. The findings aim to guide policymakers in designing sustainable management plans for Oman's fisheries. Stricter fishing rules and the use of industry taxes to control effort levels are two of the study's recommended remedies for overfishing. The objective of these strategies is to maintain long-term sustainability while balancing biological and economic returns, under the supervision of both public and private sector entities.